A new plate design to treat displaced 3-4 parts proximal humeral fractures in comparison to the most tested and used plate: clinical and radiographic study - Giuseppe Rollo; Giuseppe Porcellini; Roberto Rotini; Michele Bisaccia; Paolo Pichierri; Paolo Paladini; Enrico Guerra; Enio De Cruto; Raffaele Franzese; Predrag Grubor; Valerio Pace; Luigi Meccariello (Medicinski glasnik, 2019)
Aim: Proximal humeral fractures are common and most complex patterns currently represent a challenge for surgeons. Difficulties in obtaining good anatomical reduction (particularly of great tuberosity) often lead to unsatisfactory results; choices often fall onto prosthesis implantation against fixation options. The aim of this study was to compare a new design of proximal humeral plate with the most used plates in the treatment of these injures by analysing outcomes and complications. Methods: Two hundred patients with proximal 3 or 4 parts humeral fracture were enrolled (Neer 3-4). First group treated with PGR Plate composed of 98 patients. Second group treated with Philos Plate composed of 102 patients. Evaluation criteria were Non-Union Scoring System, duration of surgery, complications, objective quality of life and elbow function (Constant Shoulder Score), subjective quality of life and elbow function (Oxford Shoulder Score), post-op radiographs, centrum collum diaphyseal angle. Evaluation endpoint was 12 months. Results: There was no statistically significant difference between the groups with regard to the selected evaluation parameters. Achievement of good shoulder range of motion and ability to perform normal daily living activities was obtained in both groups. The PGR had a positive impact on treatment results of varuspattern of proximal humeral fractures. Conclusions: The PGR allowed good clinical and radiographic results in the treatment of proximal humeral fractures, comparable to those obtained with Philos. Also, PGR had the advantage to aid and keep the anatomical reduction of patterns of fracture involving the greater tuberosity.
Keywords: device design; internal fracture fixation; metal plating; proximal humeral fractures